(untitled) (Journal of Kidney Cancer, 2019)
There is a global variation in the incidence of renal masses with the developed nations having a greater incidence. About 80–90% of renal malignancies are renal cell carcinomas (RCC) which account for 2–4% of all cancers. In Africa and the Middle East, the age-standardized incidence for RCC is 1.8–4.8/100,000 for males and 1.2–2.2/100,000 for females. The management of renal cell cancer is challenging. A multidisciplinary approach is effective for diagnosis, staging, and treatment. Guidelines recommend active surveillance, thermal ablation, partial nephrectomy, radical nephrectomy, cytoreductive nephrectomy and immunotherapy as various modalities for various stages of RCC. However, open radical nephrectomy is most widely adopted as an option for treatment at various stages of the disease in sub-Saharan Africa due to its cost-effectiveness, applicability at various stages, and the reduced cost of follow-up. Nevertheless, most patients in the region present with the disease in the advanced stage and despite surgery the prognosis is poor.